Differences in External Morphology, Body Composition and Swimming Performance Between Hatchery- and Wild-Origin Marbled Rockfish (Sebastiscus marmoratus) - Guo, Haoyu; Zhang, Xiaofeng; Näslund, Joacim; Peng, Liye; Liu, Chenhui; Tian, Mengjia; Chai, Xuejun; Zhang, Dingyuan; Zhang, Xiumei (Frontiers in Marine Science, 2022)
Stock enhancement based on hatchery-reared fish has become one of the most common forms of management practices in marine fisheries resource restoration. However, unnatural rearing environments may cause hatchery-reared fish to diverge phenotypically from wild conspecifics, with negative consequences for post-release performance in the natural environments. To better evaluate the suitability of releasing hatchery-reared fish, it is necessary to understand the phenotypic effects of captive rearing, through comparisons with wild conspecifics. In this study, we compared body morphology, swimming performance, and biochemical body composition between hatchery-reared and wild marbled rockfish (Sebastiscus marmoratus) from the same general gene pool. The results show that the overall body profile differed significantly between the groups, with hatchery-reared individuals having a deeper body (in particular in the head and trunk regions), narrower caudal peduncles, and higher condition factor, as compared to wild conspecifics. Hatchery-reared marbled rockfish also had relatively shorter fins, for a given size. In terms of swimming performance, the hatchery-reared marbled rockfish performed worse than the wild, with slower burst swimming speeds and poorer endurance. Wild rockfish had higher body protein content but lower lipid levels compared to the hatchery-reared individuals. These results suggest that hatchery rearing conditions have a great impact on the phenotypic development, with possibly high effects on their post-release performance of the hatchery-reared marbled rockfish. Modifications for the hatchery environment and operation should be investigated with an aim to minimize the divergence in phenotypic development for production of more wild-like fish for stocking.